FAKTOR YANG BERHUBUNGAN DENGAN KEAKTIFAN KADER DALAM PEMBERIAN INFORMASI IMUNISASI DASAR - Inayati, Inna Noor; Wakano, Abuzar; Atik, Nur Sri; Witari, Ni Nyoman Deni (Ensiklopedia of Journal, 2025)
Abstract: The continuity and smooth running of posyandu activities depend heavily on the active role of cadres, who generally come from community members in the local environment. Based on an initial survey, North Sumatra Province is one of the provinces that experienced a decrease in the percentage of several types of immunization. One of the health centers with a decrease is the Sipiongot Health Center. It is known that the Sipiongot Health Center Working Area of North Padang Lawas Regency with data on the number of posyandu as many as 54 posyandu and cadres recorded as many as 232 cadres. The purpose of the study was to determine the factors associated with the activeness of cadres in providing basic immunization information. The research design used in this study was cross sectional. The research was conducted in the working area of the Sipiongot Health Center in November 2023. The study population was all posyandu cadres at the Puskesmas Sipiongot North Padang Lawas Regency in 2023 as many as 230 cadres. The sample amounted to 70 cadres. The sampling technique used in this study was purposive sampling. Data analysis was performed univariate and bivariate. The results showed a relationship between employment status (p value: 0.037) and incentives (p value: 0.01) on the activeness of cadres. It is recommended to the health center to approach and counseling related to the role of the cadres and monitor the performance of the posyandu cadres.Keywords: Immunization, Cadre, Posyandu